2017
DOI: 10.1515/jwld-2017-0015
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of groundwater vulnerability to pollution using the Kherici’s method in the Talezza plain, Collo region (NE Algeria)

Abstract: The intrinsic vulnerability of groundwater aquifers refers to their sensitivity to all contamination coming from soil surface irrespective of the nature of the polluting. In order to improve the protection of groundwater, there must be a reduction in the infiltration of contaminants towards the reservoir through the impacting factors determination of this phenomenon by means of research. There are collected models that include particular number of factors which allow the determination of a sign of groundwater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Considering scarce local groundwater studies, Attoui et al () more recently reported some nitrate data. Out of 29 samples 14 referred to nitrate ranges of <10 mg/L, 6 to the natural amount of 20 to 50 and 9 > 50 mg/L.…”
Section: Resultsmentioning
confidence: 99%
“…Considering scarce local groundwater studies, Attoui et al () more recently reported some nitrate data. Out of 29 samples 14 referred to nitrate ranges of <10 mg/L, 6 to the natural amount of 20 to 50 and 9 > 50 mg/L.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, factor 3 is associated with an opposition between chemical fertilizers and organic pollution from domestic wastewater. Factor 3 is recognized as "anthropogenic pollution" factor, which is usually identified in the urban, industry, and agriculture-intensive areas due to the domestic wastewater discharge and agricultural activities [ATTOUI et al 2017;DRAGON 2006]. Factor 4 explains the lowest variance 9.71% and Na + gave most contribution with a positive loading of 0.604.…”
Section: Discussionmentioning
confidence: 99%
“…However, the water supply deficit in the northeastern coastal aquifers, with increasing population in a high rate, has led in the last years to a search for more reliable water sources and producing, as a consequence, an intensive exploitation of the coastal aquifers in the most densely occupied area in the alluvial plain of Collo where water demand has become increasingly significant, rises [ATTOUI et al 2017]. This extreme exploitation associated with the difficulties in the process of natural recharge, due to soil impermeabilization associated with intensive urbanization has posed the system under threat of degradation, both in terms of water quantity and quality, associated to the risk of salt water intrusion [DJOUDAR et al 2008].…”
Section: Introductionmentioning
confidence: 99%